Предмет: Алгебра, автор: assema1998

Помогите
( frac{x-1}{ x^{ frac{1}{3} }-1 } + x^{ frac{1}{3} } )* frac{ x^{ frac{1}{3} }-1 }{ x^{ frac{2}{3} }-1 }

Ответы

Автор ответа: nafanya2014
0
x-1=(x ^{ frac{1}{3} }) ^{3}-1=( x^{ frac{1}{3} } -1)(x ^{ frac{2}{3} }+ x^{ frac{1}{3} } +1)

( frac{x-1}{x ^{ frac{1}{3} }-1 }+x ^{ frac{1}{3} })=   frac{( x^{ frac{1}{3} } -1)(x ^{ frac{2}{3} }+ x^{ frac{1}{3} } +1)}{x ^{ frac{1}{3} }-1}+x ^{ frac{1}{3} }=x ^{ frac{2}{3} }+ x^{ frac{1}{3} } +1+x ^{ frac{1}{3} }= \  \ =x ^{ frac{2}{3} }+ 2x^{ frac{1}{3} } +1=(x^{ frac{1}{3} } +1)^2

( frac{x-1}{x ^{ frac{1}{3} }-1 }+x ^{ frac{1}{3} })cdot  frac{x ^{ frac{1}{3} }-1}{x ^{ frac{2}{3} }-1}=(x ^{ frac{1}{3} }+1) ^{2}cdot  frac{x ^{ frac{1}{3} }-1}{(x ^{ frac{1}{3} }-1)(x ^{ frac{1}{3} }+1)}=x ^{ frac{1}{3} }+1



Похожие вопросы